Улучшение энергетических показателей тягового электропривода трамвая с двигателем постоянного тока последовательного возбуждения - Шавёлкин, Александр Алексеевич; Герасименко, Виталий Анатольевич; Кожемякин, Сергей Михайлович (НТУ "ХПИ", 2015)
Проанализированы существующие технические решения по модернизации тягового электропривода трамвая с двигателем постоянного тока последовательного возбуждения. Исследовано ослабление поля двигателя шунтированием обмотки возбуждения преобразователем на IGBT с возможностью утилизации энергии. Предложены схемы тяговых преобразователей с шунтированием и независимым включением последовательной обмотки возбуждения, позволяющие снизить потери энергии в силовых цепях, работоспособность их подтверждена математическим моделированием.

Most part of the tram park of Ukraine uses energy-intensive traction electric drive with DC motors with series excitation with rheostat control. The purpose of work is development circuit design of the traction unit on the IGBT, ensures minimum power consumption and the cost of the modernization of trams that are not exhausted their resource. Objectives: reducing the number of power semiconductors in the scheme, the development of electric drive control system and the mathematical model of the electric drive with an improved model of the magnetic circuit of the motor and the full model of traction unit, which allows to investigate the currents, voltages and power losses in the circuit. The possibility of weakening of the field using a shunt converter on IGBT, which provides an opportunity to utilization energy extracted during bypass winding. Schemes converters with independent regulation of the excitation current and shunt field winding, which allows a minimum amount IGBT to reduce energy losses in the power circuits has to offer. Formation of the current of the armature winding and the field winding is carried current hysteretic controllers. Mathematical models of electric drive systems based on the proposed converter circuits have been developed. A Model Weber-ampere characteristic of the motor, which is formed according to the current values of the currents of the field winding and the armature, has to offer. The dependence for determining the extinction coefficient for the magnetic field as a function of the set point for the armature current and the current value of the speed on the basis of the Weber-ampere characteristic of the motor and the armature EMF limit has been established. Efficiency solutions are confirmed by simulation modeling. A further area of research is an assessment of the advisability energy recovery bypass.
Improving the energy performance of the electric traction drive for tram with DC motor with series excitation
Keywords: городской электротранспорт; импульсный преобразователь; ослабление поля двигателя; обмотки возбуждения; IGBT; traction electric drive; DC motor; field weakening; pulsed DC converter; urban electric transport